Analysis of the difference in biogas volume between continuous and semi-continuous systems - Lathifa Putri Afisna; Bagas Nugroho Jati Rahadi (Researcher and Lecturer Society, 2022)
The increasing demand for energy, driven by population growth and reduced sources of oil reserves, puts pressure on every country to produce and use renewable energy as a substitute. One of the alternative energy sources is biogas, which is produced using EM4 bacteria that balance microorganisms. In this study, microorganism inoculants consisting of 90% Lactobacillus, produced from cow dung, were accommodated in an HDPE plastic container with a volume of 1 m3. Data collection was carried out from the first to the fourteenth day, with pressure data retrieved using a pressure gauge, temperature data retrieved using a thermometer gun, and the volume of biogas measured using an Arduino-based flow meter. The study found that a 1x1 meter HDPE polymer container can accommodate a maximum biogas volume of 208.12 liters. In the non-continuous system, the volume of biogas produced is not stable. The total volume of biogas produced before going through the filter for 14 days was 1075.12 liters with an average volume of 76.79 liters/day, while the total volume of biogas that had been through the filter for 14 days was 995.71 liters with an average volume of 71.12 liters/day.